Consistent Cash Flow Valuation with Tax‐Deductible Debt: a Clarification. (25th August 2011) - Dempsey, Mike
Abstract: Massari et al. (2008) argue that the weighted average cost of capital (WACC) approach to discounting expected cash flows is generally inconsistent with the adjusted present value (APV) approach. We show that their argument results from, first, taking a WACC expression that assumes a fixed level of debt in perpetuity and applying it to a scenario where the debt level varies stochastically; and, second, discounting the tax savings from stochastic debt at the rate appropriate for fixed debt. Our paper draws attention to the fundamental proposition by which such errors are avoided when cross‐referencing valuation methods. The outcome is that the APV and WACC methods are shown to be algebraically consistent with each other .